2005
DOI: 10.1002/hep.20636
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of hepatocellular carcinoma: Comparison of 7 staging systems in an American cohort

Abstract: Currently there is no consensus which staging system is best in predicting the survival of patients with hepatocellular carcinoma (HCC). The aims of this study were to identify independent predictors of survival and to compare 7 available prognostic staging systems in patients with HCC. A total of 239 consecutive patients with cirrhosis and HCC seen between January 1, 2000, and December 31, 2003, were included. Demographic, laboratory, and tumor characteristics and performance status were determined at diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
399
5
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 576 publications
(440 citation statements)
references
References 39 publications
20
399
5
12
Order By: Relevance
“…Previous studies reported that the BCLC staging system was the best model for cancer staging. 4,7,8 In contrast, other studies found that the JIS scoring system was a better model in comparison with the CLIP and BCLC staging systems. 12,13,30 Several factors may contribute to these discrepancies.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies reported that the BCLC staging system was the best model for cancer staging. 4,7,8 In contrast, other studies found that the JIS scoring system was a better model in comparison with the CLIP and BCLC staging systems. 12,13,30 Several factors may contribute to these discrepancies.…”
Section: Discussionmentioning
confidence: 93%
“…[22][23][24][25] In addition to these prospective validations, several studies have demonstrated the ability of the model. 26,27 It has been recently endorsed by numerous groups 1,21,28 and is included in the guidelines for the management of HCC from the American Association for the Study of Liver Diseases. 29 Other staging systems such as the CLIP system have also been externally validated.…”
Section: Formentioning
confidence: 99%
“…Several staging systems have been put forward without a consensus. [4][5][6] The commonly accepted International Union Against Cancer (UICC) and the American Joint Committee on Cancer (AJCC) Tumor Node Metastasis (or TNM) used in other solid tumors is of limited value in HCC as it does not take into account the competing risk of liver dysfunction which certainly plays a role in outcomes and treatment decisions. Most recently, the Barcelona Clinic Liver Cancer Staging (BCLCS) system has been adopted in many prospective studies in HCC for patient selection and provides a reasonable framework for clinical decision-making (Fig.…”
Section: The Problemmentioning
confidence: 99%